Genetic potential of grain oats in the Southern Brazil - Carvalho, Fernando Irajá F.; Barbosa, José Fernandes; Floss, Elmar L.; Ferreira Filho, Antonio Wilson P.; Franco, Francisco de A.; Federizzi, Luiz Carlos; Nodari, Rubens O. (Pesquisa Agropecuaria Brasileira, 2014)
Yield and other agronomic traits were studied in six experiments with oats (Avena sativa L.) established in the Southern Brazil, during the years 1982 to 1984. The grain yield and hectoliter wight in different genotypes showed high progress; however, plant stature and heading time did not change in the last three years. The results suggest that plant breeding programmes should release new genotypes to increase stability and yield potential.
Keywords: grain yield; genetic progress